Clinical Profile And Liver Functions In Dengue Fever - Saeeda Sadiq; Amna Mobeen; Naveed Ashraf; Fasih Hashmi; Shahzad Munir; Anam Ahmad (Journal of Rawalpindi Medical College)
Objective: This cross-sectional study explores the complex effects of dengue fever on liver functions in individuals admitted to a Federal Government Polyclinic Hospital (PGMI), in Islamabad